2013
DOI: 10.1039/c3cc41538d
|View full text |Cite
|
Sign up to set email alerts
|

Remote-control photocycloreversion of dithienylethene driven by strong push–pull azo chromophores

Abstract: In this communication, a novel photochromic molecular switch DTE-2(Azo-CN) containing both dithienylethene and push-pull azo chromophores was synthesized. The push-pull azo chromophores can significantly accelerate the ring opening of the C-C bond of DTE closed isomer when irradiated with light far away from the maximum absorption band of the DTE closed isomer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 42 publications
(15 reference statements)
0
37
0
Order By: Relevance
“…Evidently, fluorescence switching is more promising than photochromism in all-optical switches and transistors [7][8][9] . A great deal of efforts have been taken to develop novel photoswitchable fluorescent DTE derivatives with high fluorescence quantum yields (F F ), on/off ratios and switching speeds [10][11][12][13][14][15][16] . However, the performance of photoswitchable fluorescent DTEs is far from satisfactory owing to the scarcity of high-speed switching capability and large fluorescence on/off ratio.…”
mentioning
confidence: 99%
“…Evidently, fluorescence switching is more promising than photochromism in all-optical switches and transistors [7][8][9] . A great deal of efforts have been taken to develop novel photoswitchable fluorescent DTE derivatives with high fluorescence quantum yields (F F ), on/off ratios and switching speeds [10][11][12][13][14][15][16] . However, the performance of photoswitchable fluorescent DTEs is far from satisfactory owing to the scarcity of high-speed switching capability and large fluorescence on/off ratio.…”
mentioning
confidence: 99%
“…6 describes the simulated curves and Table 5 gives the main absorption bands in terms of excitation energy, oscillator strength, transition states, maximum a Experimental data is from Ref. [10]. Table 2 Relative structural parameters of the central DTE part in every molecule at ground state.…”
Section: Absorption Properties and Related Molecular Orbital Transitionsmentioning
confidence: 99%
“…It is reported that each thiophene of the DTE has been added one azobenzene (Azo) chromophore, which is an attractive molecular transducer for light driven devices and optical switches [11][12][13][14][15][16]. Thus, besides the 620 nm light, an extra irradiation at 450 nm can also significantly accelerate the ring-opening of the central C-C single bond of closed DTE ring [10]. This phenomenon is called ''remote-control'', which refers to a control of the photoswitching process by an irradiation light far away from its maximum absorption band.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The configuration changing induced by light can conspicuously influence the bulk and surface properties of the materials [1][2][3][4][5][6][7][8][9][10]. The photoresponsive properties and possible applications of azo polymers include photoinduced dichroism and birefringence [1,2], photoinduced phase transition [11], surface-relief-grating (SRG) [12,13], two-dimensional surface quasi-crystal structure [14], spontaneous surface pattern [15], photo-mechanical thin film contraction and bending [16][17][18], light-responsive block copolymer micelles [19], photoinduced colloidal deformation [20] and many others.…”
Section: Introductionmentioning
confidence: 99%